Analisis Mikrobiologi dan Praktik Higiene Sanitasi pada Penjual MP ASI Homemade Komersial di Wilayah Kerja Puskesmas Karangandong Gresik - Adelia Maulidina Choirunnisa; Amalia Ruhana (Lembaga Pengembangan Kinerja Dosen, 2026)
Complementary feeding plays a vital role in meeting the nutritional needs of infants and toddlers. However, food safety remains a concern, particularly for homemade commercial complementary foods. This study aimed to assess the microbiological quality and hygiene sanitation practices of homemade commercial complementary foods vendors in the service area of Karangandong Public Health Center, Gresik. A quantitative descriptive approach with a cross-sectional design was employed. Four homemade commercial complementary foods samples were collected from different vendors and tested for Total Plate Count (TPC) and Escherichia coli contamination. Observations and interviews were also conducted to evaluate the vendors' hygiene and sanitation practices. The results showed that three out of four homemade commercial complementary foods samples exceeded the maximum limit for microbial contamination (1 × 10² CFU/g). Two of the four samples tested positive for Escherichia coli contamination. The hygiene and sanitation practices of the vendors showed several non-conformities, categorized as minor, major, and critical. In conclusion, most homemade commercial MP-ASI products in this study did not meet established microbiological safety standards and reflected hygiene and sanitation practices that require improvement.